Indigenous food ingredients for complementary food formulations to combat infant malnutrition in Benin: a review - CHADARE, FLORA JOSIANE; Madodé, Yann Eméric; FANOU-FOGNY KLOUBOU, NADIA; Kindossi, Janvier Mêlégnonfan; Ayosso, Juvencio O.G.; Honfo, S. Hermann; KAYODÉ, POLYCARPE A.P.; Linnemann, Anita; HOUNHOUIGAN, Joseph (My University, 2018)
This paper reviews indigenous Beninese food resources as potential ingredients for complementary infant foods with the aim to develop affordable formulations for low-income households in each agro-ecological zone of the country. Potential ingredients were selected on their documented nutritional value. The selected foods encompass 347 food resources, namely 297 plant products from home gardens or collected from natural vegetation and 50 animals, either domesticated or from the wild. The compiled data reveal that the distribution of the available food resources was unbalanced between agro-ecological zones. Only a few animal ingredients are obtainable in northern Benin. Most resources are seasonal, but their availability may be extended. A high variation was observed in energy and nutrient contents. Antinutritional factors were identified in some resources, but processing techniques were reported to reduce their presence in meals. In general, ingredients from local tree foods (Adansonia digitata, Parkia biglobosa) were adequate as sources of nutrients for complementary infant foods. Based on this review, local foods for the development of complementary food formulas for Beninese infants and children may be selected for each agro-ecological zone. The approach used is exemplary for other sub-Saharan African countries in need of complementary infant foods.
Keywords: local food resource; infant food; standards; nutritional value; Benin